Perbankan Syariah Internasional: Prinsip Dan Perkembangannya - Leni Shofiyani; Nasya Wahyuni; Putri Ramadani; Khaidar Rahmaini Jamila (CV. ITTC INDONESIA, 2025)
International Islamic banking is a financial system that operates based on the principles of Islamic sharia, which rejects the practices of riba (interest), gharar (uncertainty), and maysir (speculation), and emphasizes the values ​​of justice, transparency, and partnership in every financial transaction. Along with the increasing global awareness of the importance of a stable, fair, and ethical financial system, international Islamic banking has experienced significant development, not only in countries with Muslim majorities, but also in non-Muslim countries. This phenomenon shows that Islamic principles have universal appeal because they offer an alternative financial system that is oriented towards the real sector and based on profit sharing. This study aims to analyze the fundamental principles that underlie the operations of international Islamic banking and evaluate its development and strategic role in the global financial system. The research method used is library research with a descriptive qualitative approach, through the collection and analysis of various literature sources in the form of books, national and international scientific journals, financial institution reports, and relevant official documents. The study's findings indicate that international Islamic banking plays a crucial role in enhancing the stability of the global financial system, promoting financial inclusion, and supporting sustainable economic growth through partnership-based financing and prudential principles. Furthermore, Islamic banking is considered a potential alternative financial system resilient to crises by avoiding speculative and excessive practices. Therefore, international Islamic banking has promising prospects as an integral part of the global financial system in the future.